Using planned behavior theory to understand cervical cancer screening intentions in Chinese women - Xin, Tingting; Jiang, Yuting; Li, Chunting; Ding, Xian; Zhu, Zhu; Chen, Xiao (Frontiers in Public Health, 2023)
Abstract Cervical cancer is still one of the cancers threatening the health of Chinese women with high morbidity and mortality. However, the participation rate of cervical cancer screening (CCS) among women is low due to various reasons, so it is crucial to understand the factors that influence women’s willingness to be screened for cervical cancer. This study’s goal was to understand the intention of CCS in Chinese women using the theory of planned behavior (TPB). An online questionnaire was administered to 286 women using a cross-sectional design. The questionnaire was developed based on literature review and expert panel recommendations, including demographic characteristics as well as the basic structure of the TPB. Descriptive, correlation, and multiple linear regression models were performed to identify factors associated with CCS behavior. 286 respondents completed the survey (95.3%). The mean scores for behavioral attitude, subjective norm and perceived behavioral control (PBC) were 32.50 (SD=3.30), 22.59 (SD=2.80) and 29.57 (SD=3.37). From the regression analysis, behavioral attitude (B=0.110, p=0.001), subjective norm (B=0.234, p=0.000) and PBC (B=0.171, p=0.000) were statistically significant in terms of intention. This study provided a reference for improving the intention of CCS in women. To improve the attitude of women and influential people around them towards cervical cancer screening and enhance their sense of control, thereby enhancing individual participation in cervical cancer screening.